Salmonella y tomates: preguntas y respuestas para los consumidores - Max Teplitski; Keith R. Schneider; Michelle D. Danyluk; Claudio F. Gonzalez (EDIS)
SL263-SP, a 7-page fact sheet by Max Teplitski, Keith Schneider, Michelle Danyluk, and Claudio Gonzalez, is the Spanish-language version of SL263, “Salmonella and Tomatoes: Q & A for Consumers.” It provides research-supported answers to common consumer questions about the safety of fresh fruits and vegetables in response to the recent outbreak of salmonellosis linked to the consumption of tomatoes. Includes references. Published by the UF Department of Soil and Water Science, June 2008.